2021
DOI: 10.3390/fermentation7030110
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Fermented Green Tea with Levilactobacillus brevis Capable of Producing γ-Aminobutyric Acid

Abstract: The antioxidative activity and bioactive compounds content of lactic acid fermented green tea (LFG) fermented with an outstanding GABA-producing strain under optimised fermentation conditions were evaluated. Levilactobacillus strain GTL 79 was isolated from green tea leaves and selected based on acid production, growth potential, catechin resistance, and GABA production to be applied to LFG. Through 16S rRNA gene sequence analysis, the strain was identified as Levilactobacillus brevis. The optimised conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 69 publications
2
31
0
Order By: Relevance
“…The first 3 tests followed methods described by Jin et al [ 14 ], with minor modifications, including basal medium (1% peptone, 1% glucose, 1% ethanol, 1% glycerol, 0.5% yeast extract; adjusted to a final pH of 6.8 by adding 2 M hydrochloric acid) [ 32 ] for the acid production capability test and YPM broth for the growth potential and resistance to green tea catechins tests, with incubation at 30 °C for 72 h to obtain the strains with the highest acid production and growth potential in the presence of fermentation alcohol [ 37 ]. Specific growth rates and lag times were calculated based on the values generated by Bioscreen C (Labsystems, Helsinki, Finland), using spreadsheet software (Excel 2016; Microsoft Co., Redmond, WA, USA) and a mathematical model developed by Baranyi and Roberts [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first 3 tests followed methods described by Jin et al [ 14 ], with minor modifications, including basal medium (1% peptone, 1% glucose, 1% ethanol, 1% glycerol, 0.5% yeast extract; adjusted to a final pH of 6.8 by adding 2 M hydrochloric acid) [ 32 ] for the acid production capability test and YPM broth for the growth potential and resistance to green tea catechins tests, with incubation at 30 °C for 72 h to obtain the strains with the highest acid production and growth potential in the presence of fermentation alcohol [ 37 ]. Specific growth rates and lag times were calculated based on the values generated by Bioscreen C (Labsystems, Helsinki, Finland), using spreadsheet software (Excel 2016; Microsoft Co., Redmond, WA, USA) and a mathematical model developed by Baranyi and Roberts [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Wang et al [ 13 ] reported that lactic acid fermentation using Lacticaseibacillus paracasei (formerly Lactobacillus paracasei ) enhanced the anti-obesity effect of green tea. Jin et al [ 14 ] also reported that the use of LAB increased the amounts of a variety of bioactive compounds with health-promoting effects in green tea. In the meantime, acetic acid bacteria (AAB)—such as Acetobacter pasteurianus , A. aceti , and A. lovaniensis —have been extensively utilized in the acetic acid fermentation of various food materials.…”
Section: Introductionmentioning
confidence: 99%
“…Application of selected Levilactobacillus brevis (formerly Lactobacillus brevis) strain caused significant increase in DPPH activity from 88.96% to 94.38% after the fifth day of fermentation. It is worth noting that the strain was characterized by high production of γ-aminobutyric acid (GABA) and authors concluded that initial DPPH of tea result from the content of polyphenols, while GABA and other bioactive compounds may contribute to the activity of the fermented product [62]. Although some studies indicates that LAB are present in low numbers in the Kombucha.…”
Section: Scoby Composition and Metabolic Acticitymentioning
confidence: 99%
“…After 8 days of fermentation, the antioxidant activity of fermented tea can reach up to 89.69% ( 62 ). And the DPPH scavenging ability of green tea reached 94.38% after fermentation of GABA-producing lactic acid bacteria for 5 days ( 63 ).…”
Section: Changes Of Biological Activity In Tea After Microbial Fermen...mentioning
confidence: 99%